Poppers Use and High Methaemoglobinaemia: 'Dangerous Liaisons' - Malcolm Barrangou-; Marie Gerardin; Sylvie Deheul; Marion Istvan; Marylène Guerlais; FAN; Pascale Jolliet; Thomas Dejoie; Caroline Victorri-Vigneau (MDPI AG, 2021)
Poppers are legal and largely used in France despite severe side effects, such as methaemoglobinaemia (MetHbia). Our work aimed to assess the prevalence of poppers consumers among patients with a MetHbia higher than or equal to 5% in French university hospitals and its evolution before and after the legalization of poppers in France. We conducted a national multicentre observational retrospective study. All patients for whom at least one MetHbia measurement was performed from 2012 to 2017 in university hospitals where the French addictovigilance network (FAN) is implanted were included. For each MetHbia measurement exceeding or equal to 5%, a return to the clinical file was made by the FAN to assess poppers consumption. We calculated the prevalence of MetHbia exceeding or equal to 5% and 25% and the prevalence of poppers consumption before and after the legalization. A total of 239 (0.14%) patients had a MetHbia level exceeding or equal to 5% with 25 (10.46%) cases of poppers consumption. Poppers consumption represented 68.4% (13 out of 19) of cases with MetHbia greater than or equal to 25%. Poppers consumption among patients with MetHbia exceeding or equal to 5% increased after the legalization from 4.76% to 11.67% (prevalence ratio PR = 2.45, 95% CI = [0.98-8.37], p-value = 0.190). The proportion of patients with a MetHbia level of 25% or more increased after the legalization from 4.76% to 8.63% (PR = 1.81, 95% CI = [0.68-6.82], p-value = 0.374). The use of poppers is very frequently reported by patients with MetHbia greater than or equal to 25%.